Criação de modelo virtual individualizado do osso temporal humano para impressão tridimensional - Pontes, Antonio Augusto de Lima [UNIFESP] (2016)
Dissection of the temporal bone is a fundamental part in otological training. Traditionally this training is done with temporal bones from cadavers, but currently the legal acquisition of these bones is quite complex and troublesome. At the same time, the otologic surgeon does not have a reliable way to simulate in advance the surgical procedure, since even owning an anatomical part, the difference in anatomy between individuals, creates a unique need every patient. Objective: Get custom virtual models of bones time that could be used for rapid prototyping printers to create physical models using digital tools available to any public, following defined steps. Method: We use 10 CT scans of the temporal bones of patients without ear disease, in DICOM format, with number of slices ranging from 186 to 320. In them we evaluated the presence of pre-defined anatomical structures. We employed the programs InVesalius to create the virtual model of the temporal bones, Blender to remove artifacts and Private NetFabb for optimizing models for 3D printing. Results: Of the anatomical structures sought in 10 CT scans, the stapes bone and the facial nerve canal were not always present on the images of the exams. In InVesalius program were made the reconstruction of all bone structures present in 10 CT scans; gray scale was used, which average values for the 10 reconstructions were -466 for the dark tones and 2700 for light. In the 3 CT scans that had 186 cuts, the reconstructions were not satisfactory. Still in this program was made the delimitation of the temporal bones. All reconstructions showed structural artifacts and errors. In the program Blender 3D was possible to remove all artifacts from the 7 satisfactory reconstructions. The NetFabb Private program, after analysing the models, identified and corrected structural errors in the 7 reconstructions, optimizing them for three-dimensional printing. Conclusion: It is possible to get custom virtual models of human temporal bone for actual three-dimensional printing using digital tools, following defined steps.